Training workshops on Enhancing National Climate Services (ENACTS) - Dembélé, Catherine; Zounnon, Emmanuel-Eunice; Bazie, Paulin (World Agroforestry Centre, 2021)
To help farmers coping with the negative impact of climate change CORAF and ICRAF are collaborating with various partners including AGRHYMET, Climate Change Agriculture and Food Security research program (CCAFS), the University of Reading, national meteorological and hydrological Services, nationalresearch institutes and variousNGOsinmanyWestAfrican countriesto implement innovative approaches such as climate smart agriculture (CSA), climate smart village (CSV) and Participatory Integrated Climate Services for Agriculture (PICSA). Since 2015, ICRAF has implemented PICSA approach in 8 West African countries including Benin, Burkina Faso, Ghana, Guinea, Mali, Niger, Togo, and Senegal. PICSA is an innovative approach with the objective to help farmers taking adequate decisions based on current and historical climate and meteorological data specific to their localities, also considering the options of crops, livestock and farming and other relevant livelihood options for farmers. The implementation of PICSA approach requires historical climate data and forecast locally specific to the area where each farmer is living. However, it is known that in sub-Saharan zone, the meteorological network is not very dense. Many localities lack climate information data and even where it exists, the quality is often questioned. To remedy this, ENACTS (Enhancing National Climate Services) has been developed by the Institute for Research for Development and Society (IRI) to make it possible to establish a correlation between the few observed data that exist and those of satellite images, and from this correlation, extrapolate to generate data with acceptable qualities for sites where data are missing. Based at the university of Columbia, IRI collaborates with AGRHYMET for the development and scaling of the ENACTS approach in West Africa. Along the same line, ICRAF, CORAF and AGHRYMET have agreed to organize ENACTS-MERGING training that aims to build the capacity of meteorological agents so that they can benefit from the latest performances of the ENACTS approach and be able to produce historical climate data graphs useful for PICSA implementation. A total of 20 participants coming from Benin, Burkina Faso, Cote d’Ivoire, Ghana, Mali, Niger, Nigeria, and Senegal attended the training workshop in Dakar, Senegal from June 28 to July 2, 2021. Mr. Bernard Minoungou from AGRHYMET was the main facilitator of this 5 days training workshop. Dr. Rija Faniriantsoa from IRI also followed the process and supported with one presentation on Introduction to Climate Data Tools (CDT).